1999
DOI: 10.1046/j.1537-2995.1999.39199116897.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term storage at −80°C of hematopoietic progenitor cells with 5‐percent dimethyl sulfoxide as the sole cryoprotectant

Abstract: HPCs can be cryopreserved at -80 degrees C with 5-percent DMSO and stored at -80 degrees C no longer than 6 months. A 5-percent DMSO concentration is comparable to a with 10-percent concentration in terms of recovery and MNC viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 4 publications
(3 reference statements)
5
68
0
3
Order By: Relevance
“…Long-term observations in this study confirm previous data regarding the feasibility of cryopreserving stem cells in diminished DMSO concentrations; as low as 2.2% for stem cells cryopreserved in liquid nitrogen 15 or as low as 5% for stem cells frozen and stored at -80°C. 8,9,[16][17][18] This study also confirms that the elimination of HES as an extracellular cryoprotectant can be carried out within the cryopreservation time scale of less than 6 months without affecting long-term hematologic recovery. However, we recommend caution when considering longer periods of cryopreservation.…”
Section: Outcome and Long-term Follow-up Datasupporting
confidence: 65%
See 1 more Smart Citation
“…Long-term observations in this study confirm previous data regarding the feasibility of cryopreserving stem cells in diminished DMSO concentrations; as low as 2.2% for stem cells cryopreserved in liquid nitrogen 15 or as low as 5% for stem cells frozen and stored at -80°C. 8,9,[16][17][18] This study also confirms that the elimination of HES as an extracellular cryoprotectant can be carried out within the cryopreservation time scale of less than 6 months without affecting long-term hematologic recovery. However, we recommend caution when considering longer periods of cryopreservation.…”
Section: Outcome and Long-term Follow-up Datasupporting
confidence: 65%
“…This protocol involved storage in the same mechanical freezer in solutions containing 5% or 10% DMSO as the sole cryoprotectant without HES. [7][8][9] Most studies seem to indicate that this simplified procedure is associated with a reduction in infusion toxicity and lower costs, with a similar hematopoietic reconstitution and clinical outcome to more standard protocols. However, there is little data regarding the long-term hematologic recovery and clinical course when such protocols are used.…”
mentioning
confidence: 99%
“…They did not directly compare the original and current results for each individual specimen, but the data indicated that the stem cells stored the longest had the lowest CD34 þ cell counts and CFU-GM. Other studies have also shown a decrease in CFU-GM or engraftment with long-term storage but are less applicable because of the use of less extreme freezing temperatures 17 or the use of animal models 18 and studies that report no decrease in SCP markers have been limited by relatively short median storage times. [9][10][11][12]19 In this study, recovery of SCP, TNC, cell viability and total CD34 þ cell count decreased as storage time, up to 19 years, increased.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several reports suggesting that cells can be successfully cryopreserved with minimal concentrations of DMSO [39][40][41][42][43][44][45][46][47][48][49][50][51]. For example, Zhao et al [46] showed that the use of 5% or 10% DMSO in combination with either 20% or 70% serum produced similar results during cryopreservation of fetal human liver CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%